2022
DOI: 10.3390/en15031082
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Schemes for Anomaly Detection in Solar Power Plants

Abstract: The rapid industrial growth in solar energy is gaining increasing interest in renewable power from smart grids and plants. Anomaly detection in photovoltaic (PV) systems is a demanding task. In this sense, it is vital to utilize the latest updates in machine learning technology to accurately and timely disclose different system anomalies. This paper addresses this issue by evaluating the performance of different machine learning schemes and applying them to detect anomalies on photovoltaic components. The foll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Analysis of a single-edge device has the potential to accommodate 512 solar panels within a minute. Moreover, Ibrahim et al [ 20 ] conducted a study to evaluate the efficacy of three established anomaly detection algorithms, namely Autoencoder LSTM (AE-LSTM), Facebook-Prophet, and isolation forest, in detecting anomalies on PV components. The assessment attained a maximum accuracy of 0.896.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analysis of a single-edge device has the potential to accommodate 512 solar panels within a minute. Moreover, Ibrahim et al [ 20 ] conducted a study to evaluate the efficacy of three established anomaly detection algorithms, namely Autoencoder LSTM (AE-LSTM), Facebook-Prophet, and isolation forest, in detecting anomalies on PV components. The assessment attained a maximum accuracy of 0.896.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multiple previous studies have suggested anomaly detection systems for solar power plants. An anomaly detection system based on autoencoder long short-term memory (AE-LSTM), the Facebook-Prophet, and Isolation Forest were designed to identify anomalies in the electricity generation of solar power plants [11]. An artificial neural network (ANN)-based anomaly detection system has been suggested that can predict and maintain the electricity generation of a solar power plant [12], and another method has been proposed to verify a specific outlier and its candidate for processed data on electricity generation by utilizing correlation analysis of the attribute values for solar power generation and its K-nearest neighbors (K-NN) [13].…”
Section: Related Workmentioning
confidence: 99%
“…Table 7 compares the performance of existing anomaly detection models used in solar power plants and our new model. Ibrahim [11] proposed anomaly detection for PV systems using AC power, yield, and temperature. Anomaly detection models were then developed using AE-LSTM, Facebook-Prophet, and Isolation Forest.…”
Section: Classification Algorithm and Clustering Algorithm For Data T...mentioning
confidence: 99%
“…The AE-LSTM was the most accurate model in distinguishing normal and abnormal PV system behavior. The correlation coefficients between the plant's internal and external feature parameters were calculated and used to assess the effectiveness of ML models in detecting anomalies (Ibrahim et al, 2022). However, the model does not apply to large-scale systems.…”
Section: Unsupervised Algorithmsmentioning
confidence: 99%